Ultrasensitive marker-free biomolecular THz-detection for tumor-related analytics - Richter, Merle; Loth, Yannik; Weisenstein, Christian; Wigger, Anna Katharina; Schaar, Dominik; Boßerhoff, Anja Katrin; Bolivar, Peter Haring (Frequenz, 2022)
Terahertz (THz) biosensing has emerged as an important research field, mainly driven by the resonant behavior of many biomolecules in this spectral range which holds potential for highly sensitive analyses. In this work, we present a detailed overview of our current research on THz biosensing, focusing on the development and analysis of THz biosensors based on frequency selective surfaces (FSS) for two different measurement scenarios: i) label-free, highly sensitive and selective analysis of dried biomolecules, and ii) sensitive and selective analysis in an aqueous environment. With our carefully designed THz biosensor for measurements in the dry state, we were able to indirectly measure tumor-marker MIA RNA in a concentration as low as 1.55 x 10(-12) mol/L, without the need for biochemical amplification. Our biosensor with substrate-integrated microfluidics for terahertz measurements in an aqueous environment is validated by simulations, showing that the resonance feature in the frequency response of our sensor is maintained even for measurements in water.
CRIS-Team WoS Importer:2022-11-18